The Impact of Transformational Leadership Style of School Principals and Work Motivation on Teacher Performance: An Empirical Study - Muhamad Qumarudin; Kosasih Kosasih; Yuyun Yuniarsih (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the influence of principals’ transformational leadership and teachers’ work motivation on the performance of senior high school teachers in Keerom Regency, Papua. The study addresses concerns regarding suboptimal teacher performance, limited instructional innovation, and leadership practices that remain largely administrative rather than transformational. Research Method: This study employed a quantitative approach with descriptive and inferential designs. The population consisted of 113 senior high school teachers in Keerom Regency, of whom 88 were selected using the Slovin formula with a 5% margin of error. Data were collected through structured questionnaires based on indicators of transformational leadership, work motivation, and teacher performance. The data were analyzed using multiple linear regression to examine the partial and simultaneous effects of the independent variables. Results and Discussion: The findings show that transformational leadership has a positive and significant effect on teacher performance. Work motivation also has a positive and significant effect, emerging as the dominant factor. Simultaneously, transformational leadership and work motivation significantly contribute to improving teacher performance. Implications: The findings suggest that principals should strengthen transformational leadership practices, while policymakers should support teacher motivation through professional development and conducive work environments. Originality: This study contributes by examining teacher performance in the specific context of the geographically challenging border areas of Keerom Regency, Papua.